Education as an Effort to Increase First Aid Knowledge on burns for Mothers - niken setyaningrum; Dian Nur Adkhana Sari (Journal of Health Community Service, 2025)
Cases of burns are a serious problem throughout the world. It is estimated that every year there are 180,000 deaths from burns. Emergency conditions for burns include fluid and electrolyte disturbances, pain in the burn area, shortness of breath when inhaling hot air, physical disturbances if there is a density, infection, impaired self-esteem due to scars and even death. One effort to increase knowledge is health education. This community service activity aims to increase knowledge and understanding of handling first aid in emergency burns. Activity methods include pretest, lectures with audiovisual media, leaflets and posttest. The results of knowledge show an increase in scores based on the results of the participant's posttest. Based on these activities, it can be concluded that health education with audiovisual media and leaflets can be used to increase mothers' knowledge and understanding of first aid for burns, it is hoped that participants will be able to apply and always share information with family members.